Integration of Psychology and Islamic Education in Internalizing Exemplary Values through Historical Figures of Islam - Jamilatus Zahroh; Abdul Muhid; Arif Ainur Rofiq (Academia Open, 2026)
General Background: Islamic education aspires to develop learners’ character alongside knowledge through the internalization of divine values. Specific Background: In History of Islamic Culture learning, Islamic historical figures are often taught as biographical content and chronology rather than as lived moral exemplars, contributing to a gap between cognitive knowledge and noble conduct. Knowledge Gap: A conceptual framework is needed that unites educational psychology with Islamic educational concepts to explain both the learning mechanisms and the spiritual orientation of exemplary learning. Aims: This article formulates an integrative conceptual model between psychology and Islamic education to support exemplary value internalization through Islamic historical figures. Results: Using library research and descriptive-analytical synthesis, the study proposes a three-stage framework: a cognitive stage combining information processing theory with tadabbur for deep understanding; an affective stage aligning humanistic empathy with tazkiyatun nafs to build emotional attachment; and a conative/behavioral stage integrating shaping and reinforcement with ittibaʾ to realize values in concrete actions. Novelty: The framework synthesizes psychological stages of learning with Islamic spiritual concepts into a holistic pathway that shifts Islamic Cultural History from knowledge transfer to value-oriented character formation. Implications: The model calls for teachers as facilitators and living role models, participative-reflective methods, and authentic, holistic assessment of learners’ value-oriented behavior. Highlights: A triadic pathway connects information processing with tadabbur to deepen understanding of historical narratives. Empathic learning conditions are paired with tazkiyatun nafs to cultivate emotional attachment and reflective practice. Shaping and reinforcement are linked with ittibaʾ to translate moral lessons into sustained daily actions and authentic assessment. Keywords: Value Internalization, Role Modeling, Educational Psychology, Islamic Education, Islamic Cultural History